Cationic pH-sensitive liposomes as tuberculosis subunit vaccine delivery systems: Effect of liposome composition on cellular innate immune responses - Szachniewicz, M.M.; Meijgaarden, K.E. van; Kavrik, E.; Jiskoot, W.; Bouwstra, J.A.; Haks, M.C.; Geluk, A.; Ottenhoff, T.H.M. (International immunopharmacology, 2025)
•Cationic pH-sensitive liposomes are effectively taken up by dendritic cells (DCs)•1,2-dioleoyl-sn-glycero-3-ethylphosphocholine (EPC) improves DC activation.•EPC-based pH-sensitive liposomes effectively induce activation of DCs.•pH-sensitive liposomes trigger antigen-specific IFNγ production in T-cells.•pH-sensitive liposomes are promising tuberculosis vaccine delivery candidates. Tuberculosis (TB) is a major global health problem, and the development of effective and safe vaccines is urgently needed. CD8+ T-cells play an important role alongside CD4+ T-cells in the protective immune response against TB. pH-sensitive liposomes are hypothesized to boost CD8+ T-cell responses by promoting class I presentation through a mechanism involving pH-dependent endosomal escape and the cytosolic transfer of antigens. The aim of the study was to explore the potential of pH-sensitive liposomes as a novel delivery system for a multi-stage protein subunit vaccine against TB in primary human cells. The liposomes were formulated with the fusion antigen Ag85b-ESAT6-Rv2034 (AER), which was previously shown to be effective in reducing bacterial load in the lungs HLA-DR3 transgenic mice and guinea pigs. The liposomes were assessed in vitro for cellular uptake, cell viability, upregulation of cell surface activation markers, induction of cytokine production using human monocyte-derived dendritic cells (MDDCs), and activation of human antigen-specific T-cells. Liposome DOPC:DOPE:DOBAQ:EPC (3:5:2:4 M ratio) was effectively taken up, induced several cell surface activation markers, and production of CCl3, CCL4, and TNFα in MDDCs. It also induced upregulation of CD154 and IFNγ in T-cell clones in an antigen-specific manner. Thus, cationic pH-sensitive liposome-based TB vaccines have been demonstrated to be capable of inducing robust protective Mtb-specific immune responses, positioning them as promising candidates for effectiveTBvaccination.